Penyuluhan Dagusibu Serta Pemanfaatan Biota Laut Dalam Upaya Meningkatkan Kesehatan Masyarakat di Pulau Pramuka - Dede Komarudin; Aditya Nanda Pratama; Dwi Anggraeni; Nafiatul Nurazizah; Pamela Khristi; Rizky Prasetya6; Zevania Situmorang (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2024)
Real Work Lectures (KKN) are university extracurricular activities that combine the dharma of education, research and community service in one activity. Indonesian people are used to using medicines as an effort to prevent, control or cure disease, especially during the current pandemic. However, many people often experience minor health complaints such as dizziness, fever and stomach ulcers. The low level of light services using drugs from the over-the-counter and over-the-counter drug classes is limited. It is hoped that this real work lecture (KKN) activity can increase the interest and understanding of residents in the Pulau Pramuka sub-district regarding the DAGUSIBU Effort movement for good and correct medicine and the use of marine biota to improve health, increase intelligence through the consumption of independently processed products that have high protein. The method used in this activity is a socialization method involving the community and various groups at the student level. The results obtained are that this program has run well through various programs held such as health checks, workshop activities, phytochemical screening activities for marine biota of the Ulva lactuca seaweed type, as well as DAGUSIBU extension activities.